2023
DOI: 10.2217/fvl-2022-0112
|View full text |Cite
|
Sign up to set email alerts
|

DPP-4 Inhibitors as a Savior for COVID-19 Patients with Diabetes

Abstract: Diabetic patients are at particular risk of severe COVID-19. Human dipeptidyl peptidase-4 (DPP-4) is a membrane-bound aminopeptidase that regulates insulin release by inactivating incretin. DPP-4 inhibitors (DPP-4is) are therefore used as oral anti-diabetic drugs to restore normal insulin levels. These molecules also have anti-inflammatory and anti-hypertension effects. Recent studies on the interactions of SARS-CoV-2 spike glycoprotein and DPP-4 predict a possible entry route for SARS-CoV-2. Therefore, DPP-4i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…Further studies are needed to investigate the effects of NMV‐r on these specific COVID‐19‐related outcomes. Furthermore, a previous study suggested the potential benefit of oral antidiabetic drugs, such as DPP4i in treating COVID‐19 37 . Despite the analysis matching the use of different types of antidiabetic agents between the study and control groups and performing subgroup analysis accordingly, their residual confounding effects could not be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to investigate the effects of NMV‐r on these specific COVID‐19‐related outcomes. Furthermore, a previous study suggested the potential benefit of oral antidiabetic drugs, such as DPP4i in treating COVID‐19 37 . Despite the analysis matching the use of different types of antidiabetic agents between the study and control groups and performing subgroup analysis accordingly, their residual confounding effects could not be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…They can alleviate SARS-CoV-2 cytokine storm and injury to the organs. The use of DPP-4 inhibitors in patients with SARS-CoV-2 infection was associated with the improvement of glucose levels in diabetic patients and clinical improvement and reduction of inflammatory markers in diabetic and non-diabetic patients ( 71 , 77 , 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is predicted that PCS may affect millions of people worldwide [ 1 ], mainly people with comorbidities [ 3 ], e.g., type 2 diabetes mellitus (2TDM). The symptoms of PCS are difficulty with concentration, cognitive dysfunction, amnesia, depression, fatigue and anxiety [ 3 ], and the risk factors for the persistence of neuropsychiatric symptoms in PCS are older age, female sex and the severity of comorbidities, e.g., diabetes [ 4 ], which is often associated with tachycardia, sarcopenia, microcirculatory dysfunction or organ damage [ 5 ]. PCS is therefore a phenomenon that affects life expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes is estimated to be associated with approximately 15% of patients suffering from severe COVID-19. The mortality rate in COVID-19-positive diabetic patients was reported to be 2- to 3-fold higher compared to COVID-19-negative diabetic patients [ 5 ]. The literature (studies and meta-analyses) shows higher mortality in the COVID-19-positive diabetic population compared to the COVID-19-positive non-diabetic population [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation